2016
DOI: 10.1007/s10461-016-1506-7
|View full text |Cite
|
Sign up to set email alerts
|

HIV Testing Among Internet-Using MSM in the United States: Systematic Review

Abstract: Regular HIV testing enables early identification and treatment of HIV among at-risk men who have sex with men (MSM). Characterizing HIV testing needs for Internet-using MSM informs development of Internet-facilitated testing interventions. In this systematic review we analyze HIV testing patterns among Internet-using MSM in the United States who report, through participation in an online study or survey, their HIV status as negative or unknown and identify demographic or behavioral risk factors associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 61 publications
6
76
1
2
Order By: Relevance
“…This study demonstrated that HIVST users were more like to have a higher frequency of HIV testing and regular HIV testing compared to non-HIVST users. Regular HIV testing enables early identi cation and treatment of HIV among at-risk MSM 30 . As mentioned, the US CDC recommends MSM to take up HIV testing every 3 to 6 months if they have additional HIV risk factors 31 .…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that HIVST users were more like to have a higher frequency of HIV testing and regular HIV testing compared to non-HIVST users. Regular HIV testing enables early identi cation and treatment of HIV among at-risk MSM 30 . As mentioned, the US CDC recommends MSM to take up HIV testing every 3 to 6 months if they have additional HIV risk factors 31 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analyses of HIV testing among MSM recruited online suggests that HIV-testing frequency is suboptimal and there is room for improvement. 26 The ability to target messages to specific populations, on specific apps or websites, or in specific geographic areas gives great power to public health practitioners to tailor messages for maximum impact.…”
Section: Discussionmentioning
confidence: 99%
“…Eight reviews (6%; mean quality, moderate) focused on testing for HIV, STIs, and other diseases (e.g., anal cancer). One was a meta-analysis (Noble, Jones, Bowles, DiNenno, & Tregear, 2017). Seven reviews did not focus on a specific MSM subpopulation.…”
Section: Testing For Hiv Sti and Other Diseasesmentioning
confidence: 99%
“…Of the four reviews that included descriptive data, two suggested that fear of a positive test result was a major reason for not testing (Flowers & Church, 2002;, one reported that few HIV guidelines recommended digitalrectal exams for anal cancer screening (Ong, Chen, Grulich, & Fairley, 2014), and one suggested that annual screening for pharyngeal gonorrhea can miss this diagnosis given its short duration of infection compared to chlamydia and rectal gonorrhea (Chow et al, 2016). Of the two prevalence-related reviews, one suggested that persistent high rates of STI among MSM may be due to a disconnect between screening recommendations for STI and actual screening (Lutz, 2015); the other found that 85% of Internet-using MSM had tested for HIV (Noble et al, 2017). The latter review also provided correlational data and found that age >30 years, college education, drug use, and self-identification as gay were associated with HIV testing.…”
Section: Testing For Hiv Sti and Other Diseasesmentioning
confidence: 99%